46.6k views
5 votes
Help me please .....

Help me please .....-example-1

1 Answer

2 votes

Answer:

the transformed function will be:
\mathbf{g(x)=-\sqrt{(1)/(3) x}+2}

Explanation:

We need to transform
f(x)=√(x) into g(x) using following translations

1) reflection in the x-axis

The reflection across x-axis will be:


g(x)=-√(x)

2) Horizontal shrink by a factor of 1/3

The horizontal shrink by a factor of 1/3 will make the function g(x)


g(x)=-\sqrt{(1)/(3) x}

3) Vertical translation up 2 units

The vertical translation up 2 units will make the function g(x)


g(x)=-\sqrt{(1)/(3) x}+2

So, the transformed function will be:
\mathbf{g(x)=-\sqrt{(1)/(3) x}+2}

User Ulisses
by
5.4k points